Understanding the Role, Expectations, and Challenges That Policy-Makers Face in Using Educational Research - Georgeta Ion; Simona Iftimescu; Carmen Proteasa; Elena Marin (MDPI AG, 2019)
This study provides an insight into the challenges faced in establishing a closer collaboration between educational research and its use in the policy-making process. It aims to identify the factors influencing transfer from research to policy-making and the policy-makers’ needs, expectations, and perception on the use of educational research. Thirteen semi-structured interviews were conducted with representatives of Romanian national and local institutions. Specific software was used to facilitate data management and coding. The results indicate that there is a disconnect between policy-makers’ expectations and the input they receive from the research community, as well as a lack of an institutional framework to facilitate communication and interaction between them. There are systemic blockages on both sides: politics and the cost of opportunity for decision-making, a high level of bureaucracy, limited resources and accessibility of results, a lack of financing and of institutionalized communication, as well as a lack of consultation and cooperation between the two parties. The results indicate a willingness on the policy-makers’ side to acknowledge the importance of using research to inform decisions and their role in facilitating this process. This implies that researchers have limited control over the subsequent stages and could indicate the early point in the research process when other actors should be involved in order to ensure the potential or actual impact of research on policy.